Kolaborasi Antar Stakeholders Dalam Manajemen Bencana Tanah Longsor Di Kota Semarang - Aziz Masyhuri; Hartuti Purnaweni; Augustin Rina Herawati; Budi Puspo Priyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to analyze the collaboration process between stakeholders in landslide disaster management in Gajahmungkur District, Semarang City. Collaboration between stakeholders aims to build commitment, understanding, and responsibility in increasing the effectiveness of disaster management which is analyzed through the concept of collaborative governance by Ansell & Gash (2007). Based on a descriptive qualitative research approach, this research was conducted in the city of Semarang, precisely in the district of Gajahmungkur Kecamatan. Data collection was carried out by interview and documentation techniques. Data analysis is based on four indicators of collaborative governance including: initial conditions, institutional design, facilitative leadership, to the collaborative process. The results of this study indicate that there are three stakeholders involved in the collaboration, namely local government, community groups, and also the private sector, however, in the process the coordination carried out by the three stakeholders is not effective enough, thus hindering disaster management activities. As a result of this lack of coordination, the landslide disaster in Semarang City has not been handled properly. Based on the results of the study, it can be concluded that the collaborative process carried out in landslide disaster management in Semarang City has not run optimally due to lack of coordination and lack of participation from other stakeholders outside the government sector, causing landslides to still occur frequently.